Evaluating Responsiveness of Raised Serum Ferritin for Treatment in Patients with Chronic Hepatitis C Infection (Journal of Medicine, 2019)
Background: Hepatitis C virus infection (HCV) is known as a major public health challenge across the world. There is a positive association between iron accumulation in hepatocytes and increased concentration of serum markers, including ferritin and transferrin. The study has aimed to investigate the responsiveness of increased serum ferritin levels among patients suffering HCV infection.Materials and Methods: The study has recruited 195 patients from the Hamad General Hospital, who were suffering with HCV infection. The clinical characteristics included HCV viral load, biochemical data, and parameters of iron status were evaluated among all the patients. The obtained results were quantitatively analyzed using Microsoft excel 2013.Results: The results revealed that the correlation between HCV and iron accumulation in hepatocytes is significantly interfered by the anti-viral treatment. The mean value of iron for positive PCR was calculated to be 19.93 μmol/L; and for negative PCR, the value was estimated to be 24.61 μmol/L before administration of drug. The iron level was 62.77 μmol/L among the patients with positive PCR, which is within normal range. The decrease in level of ferritin represents negative results after the drug administration. Increased levels of ALT were observed among 37.62 percent of the patients.Conclusions: The patients, suffering from chronic HCV, possess significant association with serum iron levels.J MEDICINE JAN 2020; 21 (1) : 14-19